"Assessing Familiarity of Mavrigi Song as an Intangible Cultural Heritage among People in Uzbekistan and Abroad" (Zien Journal of Social Sciences and Humanities, 2023)
This article evaluates the familiarity of the Mavrigi song cycle, an intangible cultural heritage, among people in Uzbekistan and abroad. A survey was conducted to gather data from 54 respondents of various age groups and nationalities, and the results showed that 67.9% of respondents had never heard of the Mavrigi song. However, among the respondents who were familiar with the song, more than 80.9% correctly identified the Doira as the instrument used to play the song. The article also discusses the implications of the findings, including the strengths and weaknesses of introducing the Mavrigi song to different groups of people, and provides recommendations for promoting and preserving the song as an intangible cultural heritage.